Volatile Fatty Acids (VFAs) Generated by Anaerobic Digestion Serve as Feedstock for Freshwater and Marine Oleaginous Microorganisms to Produce Biodiesel and Added-Value Compounds - Patel, Alok; Mahboubi, Amir; Horváth, Ilona Sárvári; Taherzadeh, Mohammad J.; Rova, Ulrika; Christakopoulos, Paul; Matsakas, Leonidas (Frontiers in Microbiology, 2021)
Given an increasing focus on environmental sustainability, microbial oils have been suggested as an alternative to petroleum-based products. However, microbial oil production relies on the use of costly sugar-based feedstocks. Substrate limitation, elevated costs, and risk of contamination have sparked the search for alternatives to sugar-based platforms. Volatile fatty acids are generated during anaerobic digestion of organic waste and are considered a promising substrate for microbial oil production. In the present study, two freshwater and one marine microalga along with two thraustochytrids were evaluated for their potential to produce lipids when cultivated on volatile fatty acids generated from food waste via anaerobic digestion using a membrane bioreactor. Freshwater microalgae Auxenochlorella protothecoides and Chlorella sorokiniana synthesized lipids rich in palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1), and linoleic acid (C18:2). This composition corresponds to that of soybean and jatropha oils, which are used as biodiesel feedstock. Production of added-value polyunsaturated fatty acids (PUFA) mainly omega-3 fatty acids was examined in three different marine strains: Aurantiochytrium sp. T66, Schizochytrium limacinum SR21, and Crypthecodinium cohnii. Only Aurantiochytrium sp. T66 seemed promising, generating 43.19% docosahexaenoic acid (DHA) and 13.56% docosapentaenoic acid (DPA) in total lipids. In summary, we show that A. protothecoides, C. sorokiniana, and Aurantiochytrium sp. T66 can be used for microbial oil production from food waste material.